Efficient strategies based on behavioral and electrophysiological methods for epilepsy-related gene screening in the Drosophila model - Liu, Chu-Qiao; Qu, Xiao-Chong; He, Ming-Feng; Liang, De-Hai; Xie, Shi-Ming; Zhang, Xi-Xing; Lin, Yong-Miao; Zhang, Wen-Jun; Wu, Ka-Chun; Qiao, Jing-Da (Frontiers in Molecular Neuroscience, 2023)
With the advent of trio-based whole-exome sequencing, identifying candidate genes for epilepsy has become easier, resulting in a large number of potential genes that need to be validated in a whole organism context. However, conducting animal experiments in a systematic and efficient manner remains a challenge due to their labor-intensive and time-consuming nature. To address this issue, we have developed optimized strategies for validating candidate genes in epilepsy using the Drosophila model. Our methods incorporate behavior, morphology, and electrophysiology for genetic manipulation and phenotypic examination. We used the Gal4/UAS system in combination with RNAi techniques to generate loss-of-function models. We performed a range of behavioral tests, including two previously unreported seizure phenotypes, to evaluate the seizure behavior of mutant and wild-type flies. To visualize morphological alterations in the brain, we used Gal4/UAS-GFP flies and observed them under a confocal microscope. We also implemented patch clamp recordings, including a novel electrophysiological method for studying synapse function, and improved methods for recording action currents and spontaneous EPSCs on targeted neurons or synapses. Our studies of the genes Tango14, Klp3A, Cac, and Sbf1 demonstrate the feasibility and efficiency of our screening system. In conclusion, this efficient screening system holds the potential to significantly accelerate and optimize the process of identifying candidate genes in epilepsy, particularly in conjunction with trio-based whole-exome sequencing.